AN ANALYSIS OF STUDENTS’ ABILITY IN WRITING NARRATIVE TEXTS - Dini Utami (Journal of English and Education, 2013)
This paper reports on the results of a study focusing on the analysis of students’ ability in writing narrative texts in terms of schematic structure and linguistic features. A qualitative case was used in this study. The data of this study were nine junior high school students’ narrative texts that came from low, middle, and high levels of achievement. The analysis of the data indicate that the students from low and middle achievers have insufficient knowledge of writing narrative. It can be seen from the schematic structure and linguistic features of the texts. Moreover, the students from these levels of achievement still need a lot of writing guidance from the teacher. Furthermore, for high achiever student, the teacher only needs to remind the student to read again the text for several times to avoid minor mistakes. Hence, appropriate teaching techniques and approaches should be implemented. Keywords:Narrative text, schematic structure, linguistic features